2020
DOI: 10.26434/chemrxiv.13289525.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graphene Reinforced Polyether Ether Ketone Nanocomposites for Bone Repair Applications

Abstract: To improve the performance of polyether ether ketone matrix (PEEK) in hard tissue repair and replacement applications, we fabricated graphene (G) reinforced PEEK with graded G concentrations (0.1%-5%) through injection molding. The mechanical properties, surface morphology, chemical composition and thermal stability of the composites have been characterized through universal mechanical testing, scanning electron microscopy, contact-angle measurement, transmission electron microscope, X-ray photoelectron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This may lead to agglomeration of the AgNPs and/or GO (also see Figure S2 ), leading to the raspberry-like AgNP morphology. While well dispersed nanofillers have been reported to enhance the composite mechanical properties, it is also widely recognized that agglomeration of nanofiller materials can cause local stress concentration, thus deteriorating the mechanical properties of the resulting composites [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may lead to agglomeration of the AgNPs and/or GO (also see Figure S2 ), leading to the raspberry-like AgNP morphology. While well dispersed nanofillers have been reported to enhance the composite mechanical properties, it is also widely recognized that agglomeration of nanofiller materials can cause local stress concentration, thus deteriorating the mechanical properties of the resulting composites [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, new generations of joint prostheses have shown the trend of gradually replacing metal joints with polymer joints, especially polyether-ether-ketone (PEEK) prostheses [6][7][8]. PEEK possesses good biocompatibility and high mechanical property close to the strength of natural cortical bone [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Its thermoplastic nature also allows it to be 3D printed into tissue scaffold with be-spoke geometry [21]. One major limitation of PEEK is its lack of bioactivity, which impedes its application for bone regeneration [22,23]. To address this issue, various strategies (such as surface coating or bulk reinforcement with bioactive agents) have been adopted to enhance the bioactivity of PEEK implants, a detailed review of which can be found in [24].…”
Section: Introductionmentioning
confidence: 99%